2006
DOI: 10.3797/scipharm.2006.74.159
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Interaction of Thymoquinone and Sodium Valproate in Experimental Models of Epilepsy: Reduction in Hepatotoxicity of Valproate

Abstract: The antiepileptic potential of thymoquinone (TQ) was studied in mice by using pentylenetetrazole (PTZ) and maximal electroshock seizure (MES)-induced convulsion models. In this investigation, the combined treatment of TQ and sodium valproate (SVP) was also studied. The aim of this part was to minimize SVPinduced hepatotoxic implications, by reducing its antiepileptic dose. TQ in both PTZ-and MES-models increased SVP potency. The experiments dealing with the effects of TQ on the ED 50 of SVP revealed that TQ re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 25 publications
(36 reference statements)
0
10
1
Order By: Relevance
“…Treatment of VPA with NSO extracts include of TQ (A major component t of volatile oil of Nigella species) is an antioxidant and keeps liver against VPA induced toxic damage. TQ significantly declined the AST and ALT activities (Raza et al, 2006). …”
Section: Resultsmentioning
confidence: 93%
“…Treatment of VPA with NSO extracts include of TQ (A major component t of volatile oil of Nigella species) is an antioxidant and keeps liver against VPA induced toxic damage. TQ significantly declined the AST and ALT activities (Raza et al, 2006). …”
Section: Resultsmentioning
confidence: 93%
“…The antiepileptic effects of the main constituents of NS seed have been evaluated using different agents - induced seizures (Hosseinzadeh & Parvardeh 2004 ; Raza et al. 2006 , 2008 ; Ezz et al. 2011 ), and the involvement of GABA receptors in this process has been acknowledged, as well.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the alteration of the expression of key proteins such as Bcl-2, Bax, Caspase-9, Caspase-3, and PARP-1 by TQ and Metformin were showed in conferring the therapeutic activities (Ilhan et al, 2005 ; Al-Majed et al, 2006 ). Further, Raza et al ( 2006 ) reported that TQ also diminishes sodium valproate induced hepatotoxicity. TQ synergistically enhances the efficacy of sodium valproate at doses 50 and 100 mg/kg in PTZ as well as MES models.…”
Section: Pharmacological Potentials Of Thymoquinonementioning
confidence: 99%